2021
DOI: 10.3390/ijerph18147258
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Barthel Index to Assess Activities of Daily Living before and after SARS-COVID 19 Infection of Institutionalized Nursing Home Patients

Abstract: The objective of the present study was to evaluate the activities of daily living (ADLs) using the Barthel Index before and after infection with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and also to determine whether or not the results varied according to gender. The ADLs of 68 cohabiting geriatric patients, 34 men and 34 women, in two nursing homes were measured before and after SARS-CoV-2 (Coronavirus 2019 (COVID-19)) infection. COVID-19 infection was found to affect the performance of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
1
11
1
2
Order By: Relevance
“…In their cohort (mean age 85.9 ± 6.42, 34 male/34 female) the post Covid Barthel total score was 52.30 ± 27.22 (44.56-60.04), which was higher than in the cohort analyzed here (40.2 ± 26.8), emphasizing the burden of PJI. 29 Further, the geriatric multimorbidity was considered. The results showed that patients were diagnosed with 2.7 ± .9 multimorbidity feature complexes on average and that incontinence (38.1%) and immobility (25.6%) were the most prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…In their cohort (mean age 85.9 ± 6.42, 34 male/34 female) the post Covid Barthel total score was 52.30 ± 27.22 (44.56-60.04), which was higher than in the cohort analyzed here (40.2 ± 26.8), emphasizing the burden of PJI. 29 Further, the geriatric multimorbidity was considered. The results showed that patients were diagnosed with 2.7 ± .9 multimorbidity feature complexes on average and that incontinence (38.1%) and immobility (25.6%) were the most prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…The Barthel index is an instrument used in medicine for the functional assessment of a patient [24,25]. This scale is used to measure the ability of a person to perform 10 basic ADLs; in this way, a quantitative estimate of their degree of independence can be obtained regarding ADL in institutionalized nursing home patients, for example, nutrition or walking, with a score from 0 to 100 [26].…”
Section: Methodsmentioning
confidence: 99%
“…The summarised results of the patient are described as: I) 85 to 100 points, mild dependency of a patient; II) 21 to 85 points, moderate dependency; III) 0 to 20 points, severe dependency. First described in 1965 (Mahoney, Barthel 1965), the Barthel index has been successfully used to assess daily activities in patients with different cardio-pulmonary problems, old age patients, and post-Covid patients (Trevissón-Redondo et al, 2021).…”
Section: Methodsmentioning
confidence: 99%